2017
DOI: 10.1111/jzo.12464
|View full text |Cite
|
Sign up to set email alerts
|

Food niche segregation between sympatric golden jackals and red foxes in central Bulgaria

Abstract: In Europe, the range of the golden jackal (Canis aureus) has expanded since the mid‐twentieth century, but little is known about how it interacts with other sympatric carnivores. Among European countries, Bulgaria has the largest population of golden jackals and jackal numbers have increased around two‐fold during the past two decades, particularly in lowland habitats. Larger canids often competitively exclude, or even kill, smaller sympatric ones, especially when guild dynamics are in flux due to population r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 54 publications
1
12
1
Order By: Relevance
“…The consumption of medium-sized mammals, the third shared food category, was of secondary importance for both canids. Generally, the food habits of both species were similar to those reported by previous researches, in particular those carried out in more natural and heterogeneous landscapes [ 88 , 89 ]. Conversely in human-modified landscapes, e.g.…”
Section: Discussionsupporting
confidence: 84%
“…The consumption of medium-sized mammals, the third shared food category, was of secondary importance for both canids. Generally, the food habits of both species were similar to those reported by previous researches, in particular those carried out in more natural and heterogeneous landscapes [ 88 , 89 ]. Conversely in human-modified landscapes, e.g.…”
Section: Discussionsupporting
confidence: 84%
“…This effect, however, was only reported once in our literature search by a study comparing mesopredator diet overlap between two study areas with a large difference in grey wolf, Canis lupus , density due to a wolf‐control program (Sivy et al ., 2017). Additionally, this effect can be partially mitigated by provisioning carcasses resulting from hunting activities, as we found in two studies (Barrull et al ., 2014; Tsunoda et al ., 2017), or livestock practices (Cortés‐Avizanda, Carrete & Donázar, 2010). However, artificial disposal of carrion may inadvertently affect non‐target species (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Golden jackals have expanded northward in Europe (Arnold et al 2012), as evidenced by their establishment and potential reproduction in the Baltic region (Kowalczyk et al 2020), which has raised concerns for their management in newly colonised countries (Trouwborst et al 2015). Our finding that jackals consume small mammals to a greater extent at higher latitudes indicates potential food resource competition with other rodentivorous carnivores, such as the red fox Vulpes vulpes; previous studies have demonstrated food competition between these two canids in southern European and Mediterranean regions (Scheinin et al 2006, Farkas et al 2017, Tsunoda et al 2017. Furthermore, disruption to the availability of the staple food of jackals (i.e.…”
Section: Discussionmentioning
confidence: 55%